2018
DOI: 10.1016/j.chemgeo.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Acid-base properties of kaolinite, montmorillonite and illite at marine ionic strength

Abstract: In marginal marine settings, understanding the role that clay minerals play in the transfer of metal cations from the water column to the seafloor is important if the composition of modern muds in the ocean is used as a proxy for the precursors of ancient shale deposits. In this study, we conducted potentiometric titrations of three naturally abundant clay minerals (kaolinite, montmorillonite and illite) in 0.56 M NaCl electrolyte solutions to ascertain the surface reactivity of each clay mineral at seawater i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 71 publications
3
12
0
Order By: Relevance
“…Natural montmorillonite usually exhibits a negative surface charge at seawater pH, which inhibits the adsorption of uranyl because of charge repulsion . To address this disadvantage, in this study, a montmorillonite substance that exhibits neutral charge at weakly alkalescent pH was selected to develop the target fiber material.…”
Section: Resultsmentioning
confidence: 99%
“…Natural montmorillonite usually exhibits a negative surface charge at seawater pH, which inhibits the adsorption of uranyl because of charge repulsion . To address this disadvantage, in this study, a montmorillonite substance that exhibits neutral charge at weakly alkalescent pH was selected to develop the target fiber material.…”
Section: Resultsmentioning
confidence: 99%
“…Potentiometric titration has been used to quantify the density of active reaction sites of clay minerals and determine the surface acidity constants (Ka) of those sites 25,26,43,44,46,5461 . The protonation behaviors of three different kaolinite or montmorillonite (untreated, acid-spilled, and alkali-spilled) were investigated using an automatic potentiometric titrator (G10S, Mettler-Toledo, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Although this work is currently being conducted, there are existing data available that consider clay mineral reactivity in such settings. For instance, experimental results of Cd adsorption onto montmorillonite showed that almost 90% of Cd adsorbed onto montmorillonite at pH=6 and at 0.001 M ionic strength (Gu et al, 2010), while this number decreased to only 10% if ionic strength was increased to mimic seawater (0.56 M) (Liu et al, 2018). The increase of pH has inverse effect with IS, where the increase of pH from 6 to 8 results in an additional 40% of Cd adsorption (Liu et al, 2018).…”
Section: Conclusion and Environmental Implicationsmentioning
confidence: 99%
“…Over the past decade, our understanding of the mechanisms underpinning the adsorption of ions to geologic media has considerably improved through the use of sorption isotherms and experimentally-derived surface complexation modeling (e.g., Borrok and Fein, 2005;Alessi and Fein, 2010;Wang et al, 2010;Komárek et al, 2015;Liu et al, 2015;Alam et al, 2018;Liu et al, 2018;). Adsorption is generally governed by two parameters: the surface charge properties of the adsorbent and the chemical complexation of aqueous adsorbates onto specific surface functional groups (Dzombak and Morel, 1990).…”
Section: Introductionmentioning
confidence: 99%